Body-Worn Versus Bell-and-Pad Alarm Device for the Management of Monosymptomatic Nocturnal Enuresis in Children: A Randomized Controlled Trial. Issue 5 (September 2020) - Peck, Blake; Peck, Bronwyn; Harvey, Jack; Green, Andrea; Svedas, Kerrie; Whitaker, Shirley; Nethercote, Mark; Rosemarie Shea,
Abstract : PURPOSE: The purpose of this study was to compare the effectiveness of bell-and-pad alarm therapy to body-worn alarm therapy for the management of monosymptomatic enuresis in children 6 to 16 years of age. DESIGN: A prospective, randomized, adaptive clinical control trial. SUBJECTS AND SETTING: The sample comprised 86 children who attended a continence clinic for treatment of monosymptomatic enuresis and met the criteria for enuresis alarm therapy as per International Children's Continence Society (ICCS) guidelines. Subjects were randomly allocated to an experimental group (body-worn alarm, n = 41) or a control group (bell-and-pad alarm, n = 45). The study setting was a single-site specialist continence service in regional Victoria, Australia. Treatment was administered in the child's home. METHODS: Alarm therapy was administered by the child and/or parent for an initial period of 8 weeks at which time the child underwent a review with the continence nurse specialist. If the child had achieved 14 consecutive dry nights, the therapy was deemed successful and ceased. Children who had not become dry continued therapy for a further 8 weeks up to a maximum of 16 weeks, with a final review was instituted. Each child kept a diary for the duration of alarm therapy to report on frequency of wet/dry nights, times of alarm, response to alarm, and response to sensation to void (without alarm). The 2 types of alarm devices were compared with respect to categorical variables using dichotomous cross-tabulations and χ 2 tests of independence based on the most positive outcome versus the other outcomes. RESULTS: Dryness in accordance with the criteria outlined by the ICCS guidelines was achieved in 18 children (43.9%) in the body-worn alarm group versus 29 children (64.4%) in the routine (bell-and-pad) group ( P = .056). The bell-and-pad alarm performed better on 7 out of the 9 indicators, including the primary outcome measure of the child attained dryness for 14 nights or more, nightly alarm use, alarm woke child, alarm woke parent ( P = .022), false (positive) alarms ( P = .039), child turned alarm off and went back to sleep ( P = .003), and child was compliant with alarm use. The body-worn device produced higher proportions of the most positive outcomes for 2 of the 9 indicators: relapse ( P = .076) and false (negative) nonalarms ( P = .066). CONCLUSIONS: Study findings suggests that the bell-and-pad alarm is preferable to the body-worn alarm. Additional research is recommended using other body-worn alarm devices across a larger population in order to establish the more definitive findings needed for clinical decision-making.